Bulgaria Public Expenditure Issues and Directions for Reform - World Bank (Washington, DC, 2013)
The study is the first-ever Public Expenditure and Institutional Review (PEIR) on Bulgaria by the World Bank. It outlines public expenditure issues, and policy directions to improve the efficiency, and effectiveness of public expenditures in the country. To this end, it assesses fiscal sustainability, and analyzes the public expenditures, and their institutional framework. Bulgaria has made substantial progress toward long-term macroeconomic stability, but important challenges remain in the five sectors analyzed - education, health, social protection, the state railways, and energy sectors. It also analyses the institutional challenges in public expenditure management.